Strategic communications and the challenges of the post 9/11 world / Philip M. Taylor - Taylor, Philip M. (Centre for Media and Information Warfare Studies, 2008)
The 21st century has brought us significant challenges that would be unrecognisable to our forefathers a century ago. In 1907, women could not vote - indeed many men could not vote unless they possessed property or land. In 1907, wealthier people in the western world were just coming to terms with the wonders of new communications technologies such as the land-line telephone while the poorer ones were marveling at all sorts of moving images being produced for the nickelodeons or cinemas that were springing up in the towns and cities. Strategic Communications is a phrase that encapsulates a nation state's attempt to co-ordinate all the elements of its informational power. It involves Public Affairs at home and abroad, Public Diplomacy and Information Operations all working in harmony and with the same voice. If done well, it can communicate national messages explaining and justifying foreign policy actions.